The effect of whole-body cryostimulation on the prooxidant-antioxidant balance in blood of elite kayakers after training - Wozniak, A.; Wozniak, B.; Drewa, G.; Mila-Kierzenkowska, C. (European Journal of Applied Physiology, 2007)
The effect of whole-body cryostimulation prior to kayak training on the prooxidant-antioxidant balance was evaluated and compared to the effect of a single cryostimulation treatment in untrained men. The kayakers underwent a ten-day training cycle with pre-training daily whole-body cryostimulation for three min (temperature: -120 to -140°C) and training without cryostimulation as a control. Blood samples were obtained before and after the sixth and the tenth day of training and from the untrained men before and 20 min after cryostimulation. In untrained men cryostimulation induced an increase in the activity of superoxide dismutase (SOD) by 36% (P < 0.001) and glutathione peroxidase (GPx) by 68% (P < 0.01) in the erythrocytes and an increase in the conjugated dienes (CD) in plasma by 36% (P < 0.05) and in the erythrocytes by 71% (P < 0.001). In the kayakers comparing both types of training after the sixth day, the level of CD in plasma was 46 (P < 0.001) and 40% (P < 0.01) lower in erythrocytes, and the concentration of thiobarbituric acid-reactive substances in plasma was 24% (P < 0.05) lower with pre-training cryostimulation. After the sixth day of training with cryostimulation, SOD activity was also 47% (P < 0.001) lower, while GPx activity after the tenth day was reduced by more than 50% (P < 0.01) as compared to control training. Whole-body cryostimulation per se stimulates the generation of reactive oxygen species. Yet, the oxidative stress induced by kayak training was reduced by prior exposure to extremely low temperatures.